Ecologia de interações entre Coragyps atratus (Bechstein, 1793) e Caracara plancus (Miller, 1777) no município de Uberlândia (MG) - Souto, Henrique Nazareth (2008)
Although seldom reported, necrophagy is a relatively common phenomenon in nature. Among necrophagous vertebrates, scavengers are the only ones who have a diet composed almost exclusively by carrion. There are five species of scavengers recorded in Brazil and in some Brazilian regions these species can live in sympatry, interacting with each other and with species of Falconiformes. The aims of this study were: 1. to investigate the use of perches and food resources by necrophagous birds in different areas of Uberlândia city (MG), and 2. to establish the types of interactions (intra- and inter-specific) between the studied populations. The research was performed between December 2006 and December 2007, though field observations were concentrated in the dry period (June to September 2007). Three types of habitats were selected for the field work (urban environment, urban-rural environment and rural environment). The observations followed focal animal ad libitum analises, and were carried out from 9 am to 6 pm. All areas were sampled monthly, performing 90 hours of observation (30 hours in each area). Two species of necrophagous birds were recorded: Coragyps atratus (Black Vulture) and Caracara plancus (Crested Caracara). The rural-urban environment showed higher frequency of records of scavengers and Crested caracara using perches (5646). Moreover, the urban environment served as a deposit of waste and carcass of animals stemming both from urban environments as well as rural environments. Interactions for food were often marked by agonistic interactions, although there were displays which prevent disputes, such as warning postures and sounds production (including vocalization ). Interspecific allopreening was recorded at a higher frequency than expected and probably occurs as a way of rapprochement between Crested caracara and Black vultures when grouping in mixed flock. These mixed flocks seemed to be favored by the surveillance ability of the Crested caracara and because of its vocalization ability and thus producing scream of warning, useful for the flock.